063 TIMING OF STAGED INTERVENTION FOR NON-CULPRIT DISEASE IN PATIENTS WITH MULTI-VESSEL DISEASE UNDERGOING PPCI FOR STEMI. (24th May 2013) - Fung, K; Koganti, S; Jones, D A; Rathod, K S; Gallagher, S; Jain, A; Knight, C J; Mathur, A; Amersey, R; Weerackody, R; Wragg, A
Abstract : Background: European guidelines state that with the exception of cardiogenic shock, percutaneous coronary intervention (PCI) for ST elevation myocardial infarction (STEMI) should be limited to the culprit artery. Although there is no robust randomised controlled trial data available there is a general consensus that non-culprit coronary artery lesions identified at the time of STEMI should be treated in a staged manner. Whilst there is general consensus on the above; currently neither guidelines nor evidence exist regarding the optimal time for staged PCI. Our aim was to compare outcomes in patients who underwent staged PCI either as an in-patient or as an out-patient within 6 weeks time following a STEMI. Methods: This was an observational cohort study of 983 patients with multi-vessel disease who underwent primary PCI from 2007 to 2011. Patients with previous CABG, cardiogenic shock were excluded. 102 patients were managed with staged intervention. The primary outcome was major adverse cardiac events (all cause mortality, myocardial infarction, target vessel revascularisation and stroke). Follow-up was for a median of 3.2 years (IQR range 2.0–4.4 years). Results: 24 (23.5%) patients underwent in-patient staged PCI with 78 (76.5%) patients undergoing their intervention within 6 weeks of hospital discharge. Differences in baseline characteristics are outlined in table 1 . Patients who underwent in-patient staged PCI were older compared to those having 6 week staged procedures. (66.1±10.4 vs 59.2±10.6, p=0.02). Otherwise there were no other differences in baseline characteristics. Unadjusted Kaplan-Meier analysis revealed no significant difference in the 3-year event rates between patients undergoing in-patient and 6 week staged procedures (figure 1 ). Un-adjusted Cox analysis demonstrated no difference in 3 year outcomes between in-patient and 6 week procedures (HR 0.84 (95% CI 0.27 to 2.61)), which persisted after multivariate adjustment ((HR 0.60 (95% CI 0.12 to 2.96)) (factors corrected for: previous MI, DM, access, age, EF, eGFR, DES use, gender, previous CVA, PVD). Conclusions: This observational data suggests that staged procedures performed as an in-patient or at 6 weeks post discharge are associated with similar outcomes in STEMI patients with multi-vessel disease undergoing primary PCI.